Contralateral inclinatory approach for decompression of the lateral recess and same-level foraminal lesions using unilateral biportal endoscopy: A technical report - Tian, Dasheng; Zhu, Bin; Liu, Jianjun; Chen, Lei; Sun, Yisong; Zhong, Huazhang; Jing, Juehua (Frontiers in Surgery, 2022)
Objective Unilateral biportal endoscopic (UBE)surgery is being increasingly adopted as a minimally invasive technique. The purpose of the current study was to introduce a novel surgical technique for lateral recess and same-level foraminal decompression by the contralateral inclinatory approach with unilateral biportal endoscopy(CIA-UBE) at the lumbar level. Methods Between January 2020 and February 2022, 10 patients suffering from lateral recess and same-level foraminal stenosis at the lumbar level underwent UBE surgery by contralateral inclinatory approach (CIA-UBE). Magnetic resonance imaging (MRI) scans were examined after surgery to measure the cross-sectional area (CSA) of the spinal canal (CSA-SC), the CSA of the intervertebral foramen (CSA-IVF), and the CSA of the facet joint (CSA-FJ). Postoperative radiologic images using computed tomography (CT) were obtained to investigate the existence of facet joint violation. Clinical outcomes were assessed using Oswestry Disability Index (ODI) scores and visual analogue scale (VAS) scores for buttock and radicular pain. Results Ten levels were decompressed, and the mean age of the patients was 56.92 ± 13.26 years. The mean follow-up period was 7.60 ± 4.47 months. The average operative time was 85.14 ± 25.65 min. Postoperative CT and MRI revealed ideal neural decompression of the treated segments in all patients. CSA-IVF and CSA-FJ improved significantly, indicating good foraminal and lateral recess decompression with less damage to facet joints. Preoperative VAS and ODI scores improved significantly after surgery. Conclusion CIA-UBE may be an effective surgical treatment of the lateral recess and same-level foraminal stenosis at the lumbar level, which provides successful surgical decompression for traversing and exiting nerve roots with a better operative view and easier surgical manipulation. This approach may also help to maximize the preservation of the facet joint.